Topological Aspects of Certain Covalent Organic Frameworks and Metal Organic Frameworks. (29th June 2022) - Zhang, Guoping; Azeem, Mehran; Aslam, Adnan; Yousaf, Shamaila; Kanwal, Salma
Abstract : Topological indices are numerical numbers assigned to molecular graphs and are expected to predict certain of its physical or chemical properties. Metal-organic frameworks (MOFs) are inorganic/organic porous crystalline materials with a regular array of positively charged metal ions which surrounds organic linkers. Covalent organic frameworks (COFs) are a class of organic polymers with highly ordered structure and permanent porosity. In this work, we have computed some degree-based topological indices of naphthalene metal-organic frameworks and thiophene-based covalent triazine framework.